(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of ovarian tumors diagnosed as benign preoperatively but confirmed malignant or borderline after surgery at Hanoi Obstetrics and Gynecology Hospital. Method: This descriptive case series included 86 patients who underwent surgery between January 2020 and December 2024. Results: Among 5233 patients preoperatively diagnosed with benign ovarian tumors, 86 patients (1.6%) were malignant or borderline on postoperative pathology. Most were of reproductive age. The leading symptom was abdominal pain (54.7%), followed by menstrual and urinary disorders. On examination, 87.2% had unilateral tumors, 53.5% with ill-defined margins, 72.1% immobile, and 48.8% painful on palpation. Intraoperatively, 5.8% showed papillary growth with neovascularization, 26.7% adhesions, 3.5% rupture, 12.8% ascites, and 22.1% at least one suspicious malignant feature. Imaging findings showed that 46.5% were classified as O-RADS 4-5. Elevated CA-125 occurred in 52.3%, and 40.7% had a high-risk ROMA score. Conclusion: Ovarian tumors misclassified as benign preoperatively but confirmed malignant or borderline postoperatively often presented with clinical symptoms, were mainly O-RADS 4-5, and nearly half had high-risk ROMA scores. The intraoperative detection rate of malignant features remained low.